Primary intra osseous venous malformation of nasal bone: A rare case report - Ajit Kumar Pati; Bibhuti Bhusan Nayak; Arun Kumar Choudhury; Debesh Kumar Rout (Indian Journal of Plastic Surgery)
Primary intra osseous venous malformation with involvement of nasal bone is a rare phenomenon. Nasal bone intraosseous venous malformation on a back ground of port wine stain of face has not been reported in the available literature. We report the very rare case of intraosseous venous malformation of left nasal bone developing on a background of port wine stain of face, its diagnosis, pathology, management and review of literature.